ANTARA KUASA KEBOHONGAN DAN KEBEBASAN BEROPINI WARGA: ANALISIS WACANA FOUCAULDIAN PADA HOAKS PANDEMI CORONA DI INDONESIA - Adiputra, Wisnu Martha (Interaksi: Jurnal Ilmu Komunikasi, 2021)
This research tried to discuss the corona pandemic hoax in the vortex of the paradox of excessive freedom and political rights of citizens in the digital communication process which can be observed, among others, through the government's efforts to report hoaxes about the corona pandemic. The purpose of this research is to under-stand the hoax discourse of the corona pandemic from a Foucauldian perspective that is attached to power and identity in the Monthly Hoax Report conducted by the Ministry of Information and Communication of the Republic of Indonesia. This re-search used the Foucauldian discourse analysis method which uses a variety of con-cepts, including: power, identity, knowledge, dominant discourse and counter-discourse. The results of the research show that there are five unique stages of dis-course analysis, namely the corona pandemic hoax, which is a set of regular and systematic statements through social media that are not detailed, has a variety and production rules that only consist of two types, the powers that are said and those that may be conveyed have in common with the character of the post-truth era, a new space of power that emerges through technological devices and sociocultural con-texts, and connects both material and discursive aspects at the same time to new media artifacts and potential negative effects on citizens